PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA SEVEN BARBERSHOP DI BIREUEN - Nisa, Khairun; Ritonga, Nursakinah (Program Studi Administrasi Bisnis, 2022)
This study aims to determine the effect of service quality and price on customer satisfaction at Seven barbershops in Bireuen. The data used in this research is primary data of 100 Seven Barbershop consumers. The sampling technique used is a technique based on convenience. The method used to analyze the relationship between the independent variables and the dependent variable is a multiple linear regression method. The results of the research partially show that service quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction.